2022
DOI: 10.1186/s12891-022-05165-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiological evaluation of cage subsidence following oblique lumbar interbody fusion combined with anterolateral fixation

Abstract: Background Cage subsidence (CS) was previously reported as one of the most common complications following oblique lumbar interbody fusion (OLIF). We aimed to assess the impacts of CS on surgical results following OLIF combined with anterolateral fixation, and determine its radiological characteristics as well as related risk factors. Methods Two hundred and forty-two patients who underwent OLIF at L4-5 and with a minimum 12 months follow-up were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Controversies remained whether subsidence would directly contribute to radiculopathy recurrence and lead to enhanced risk of revision surgery. As illustrated previously, 6 severe cage subsidence (>4 mm) was tightly associated with worse patient-reported indicators including VAS and ODI, leading to lower fusion rate in long-term follow-up. Even the moderate subsidence (2-4 mm) would result in transient clinical worsening compared with the mild (<2 mm).…”
Section: Advantages Of Rlps In Restricting Postoperative Cagesupporting
confidence: 54%
“…Controversies remained whether subsidence would directly contribute to radiculopathy recurrence and lead to enhanced risk of revision surgery. As illustrated previously, 6 severe cage subsidence (>4 mm) was tightly associated with worse patient-reported indicators including VAS and ODI, leading to lower fusion rate in long-term follow-up. Even the moderate subsidence (2-4 mm) would result in transient clinical worsening compared with the mild (<2 mm).…”
Section: Advantages Of Rlps In Restricting Postoperative Cagesupporting
confidence: 54%
“…Previous studies have shown that endplate vBMD (EP‐vBMD) measured by QCT with a 5 mm height ROI can be related to the cage subsidence of XLIF better compared to that of cancellous vBMD 15,16 . Similar studies on oblique lumbar interbody fusion (OLIF) also indicate that endplate injury is a vital risk factor of cage subsidence 17 . However, the osseous endplate thickness range is 0.35–1.03 mm, implying that the 5 mm height mainly comprises the trabecular bone 18–21 .…”
Section: Introductionmentioning
confidence: 93%
“…There was an almost two-fold increased odds of proximal and distal junctional kyphosis in patients with osteopenia and osteoporosis (OR 1.95 and OR 1.88), respectively. 14 Zhao et al 15 reported on 242 patients undergoing oblique lumbar interbody fusion and found that osteoporosis was a significant risk factor for cage subsidence (OR = 6.0). The poor outcomes associated with osteoporosis have been reported both in the lumbar and the cervical spine.…”
Section: Rational For Preoperative Screening and Treatmentmentioning
confidence: 99%